Analisis Konsumsi Bahan Bakar Alat Gali Muat-Angkut pada Kegiatan Pengupasan Overburden PIT Seloklai: PT. Mitra Indah Lestari Kota Samarinda - Harjuni Hasan; Albertus Juvensius Pontus; Roland Fatar Fernados Sirait; Agus Winarno; Henny Magdalena; Revia Oktaviani (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Fuel consumption is a necessity in moving mechanical equipment, where fuel consumption is influenced by road conditions, horsepower, and load factors. PT. Mitra Indah Lestari uses Hyundai 480 and Sany750-H excavators. The transport equipment used is Wechai WT90, Tonly TLD90, and Quester CWE 330. This study uses a quantitative method and obtains fuel consumption results, where the fuel consumption of the Hyundai 480 and Sany 750-H excavators is 37.89 liters/hour and 59.91 liters/hour, respectively. The fuel consumption of the Wechai WT90, Tonly TLD90, and Quester CWE 330 transport equipment is 25.19 liters/hour; 27.53 liters/hour; and 10.66 liters/hour, respectively.